Turnaround Time of Container Vessels at Chattogram Port: Review and Assessment (BIMRAD Journal, 2025)
Despite opportunities, Bangladesh has failed to become a regional hub or meet domestic demand to strengthen her national interest. The fact that the existing port management and infrastructure is proved inappropriate in present day’s context let alone future context. Presently, vessel turnaround time is one of the global indexes of port efficiency. It is at present higher in Chattogram Port compared to international standard. The main objective of the study was to identify key determinant issues affecting the turnaround time of container vessels at Chattogram port. The study was intended to be descriptive and explanatory using primary and secondary data. Primary data was obtained using questionnaires, structured and semi-structured interviews, and limited observations while secondary data was sourced from port officials, website and libraries. The study findings indicates that direct delivery of export containers onboard, lack of export stow plan, stripping of Less Container Load (LCL) and Full Container Load (FCL) (except 37 items) containers, weak hinterland connectivity, poor IT infrastructure, inefficient gate operations, customs non-cooperation are the challenging issues that Chattogram Port is facing. It is expected that this research make an important contribution in improving turnaround time of container vessels and offering CPA an effective platform for identification of possible future directions. Emphasis has been given on having a “National Port Policy”, robust hinterland connectivity, cent percent “on chassis” delivery, strong IT infrastructure. The study recommends for a “National Port Policy”, maintaining firm cut off time and export stow plan, patronizing rail and waterways connectivity to reduce the turnaround time of container vessels.BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-85-128